Nexus among Renewable Energy, Economic Growth, Technology Innovation, CO2 Emissions, and Life Expectancy in NAFTA: What’s the Forum’s Response Amid Time Frequencies? - Fumey, Michael Provide; Ansah, Mordecai Akondoh; Taha, Amjad Issa; Sahin, Zekeriya; Sackitey, Gabriel Mordzifa; Yeboah, Samuel Duku (Econjournals, 2025)
This study examines the nexus between renewable energy (RE), economic growth (ECOG), technological innovation (TEI), CO2 emissions, urbanization (URB), and life expectancy (LEX) in NAFTA countries driven by the sustainable development framework. Using advanced wavelet coherence with data from 1990M1-2023M12, along with WAMC techniques, the analysis revealed intricate temporal and frequency-based interactions. Technological innovation and renewable energy boost life expectancy by reducing environmental degradation. As for urbanization and economic growth, these modified results anticipate dependent variables by the quality of infrastructure and policies. In the short run, tested causality relationships between variables show non-directional, while medium-and long-term scenarios evidence mutual reinforcement of the variables with life expectancy leading to renewable energy adoption and emissions reduction. The tests confirm WAMC’s almost perfect integration of factors within time scales, stressing thus their collective outcome on life expectancy. Therefore, this study emphasizes the status of appropriate sustainable policies integrating health, energy, and environmental objectives and creating effective measures toward long-term sustainability in NAFTA. © 2025, Econjournals. All rights reserved.
Keywords: Life Expectancy; NAFTA fications: Q18; Public Health; Q42; Renewable Energy; Technology Innovations